Analisis Kualitas E-Service: Studi Kasus pada Layanan Berbasis Aplikasi SEVIMA di Politeknik Negeri Fakfak - Muh. Irvan Nur Iva; Herman H; Rahayu Rahayu; Andi Asrifan; Ummi Kalsum Syam (Jurnal Ilmu Administrasi Negara, 2025)
As a relatively new e-service platform, this study aims to analyze the quality of e-service provided by the SEVIMA application as an academic service system at Politeknik Negeri Fakfak. The research is based on the importance of digital service effectiveness in supporting efficient and transparent academic governance. This study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and then analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing and verification. The findings indicate that the overall quality of SEVIMA’s e-service is considered good, particularly in the dimensions of reliability and assurance. However, improvements are still needed in user interface, responsiveness, and customization. Furthermore, users’ digital literacy and the discipline of lecturers and administrators were found to influence the effectiveness of the service. The study concludes that feature optimization, enhancement of digital literacy, and institutional support are key factors in improving the quality of digital-based academic services in higher education.